NATIONAL TRADITIONS OF CHECHEN AND INGUSH FAMILIES IN PROTECTION OF MOTHER’S AND CHILD’S HEALTH - L.V. Abol’yan; F.M. Evloeva (Вопросы современной педиатрии, 2010)
Authors describe family relations and traditions of Chechens in Ingush from ancient times to present (traditional obstetrics, delivery ceremonies, child’s management and feeding) and make a conclusion that family was and now is basic social institute of these nations. These people saved traditional way of living and norms of demographic behavior to the highest degree then other nations in Russia. High prevalence and prolonged period of breast feeding in Chechen and Ingush Republics (compared to other districts of Russian Federation) can be explained by their cultural and ethnical peculiarities. Key words: breast feeding, Chechen, Ingush, national tradition, obstetrics service, childhood.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2010;9(5):138-141)